Implementation Strategy For Fishery Processing Business Based On Blue Economy - Jani Arbakala; Sundjoto Sundjoto; Angky Soedrijanto; Untung Tamsil (PT. BATARI EDU CALYA, 2025)
This study investigates the readiness and capacity of the East Fakfak district community to transform fish into micro-small scale business products, aiming to contribute to the blue economy's development and enhance their welfare. Employing a semi-qualitative research approach through surveys, the research team, including surveyors, engaged in direct observation and conducted comprehensive interviews across all villages in East Fakfak. The objective was to assess the community's preparedness to process fish into preserved products that are marketable, high-quality, and possess unique organoleptic qualities characteristic of Fakfak. The analysis revealed a prevalent unfamiliarity among the East Fakfak district inhabitants with fish processing technologies. A traditional preference for consuming fresh fish, attributed to the ease of access to fish resources, has significantly hampered the advancement of fishery product processing in the region. This study underscores a critical need for introducing and fostering fish processing knowledge and technologies among the community. By educating and equipping the local populace with the necessary skills and resources to undertake sustainable fish processing, there lies a potential to unlock a new avenue for economic development. Such initiatives would not only diversify income sources but also ensure the longevity and sustainability of fishery resources, pivotal to the prosperity of East Fakfak's blue economy